Analisis Pengaruh Kualitas Produk, Citra Perusahaan dan Kepercayaan Konsumen Terhadap Kepuasan Konsumen Produk Online - Marina Malian (Program Studi Manajemen Universitas Muslim Maros, 2021)
This study aims to analyze partially and simultaneously the influence of product quality, brand image and consumer trust on customer satisfaction. Including quantitative research using the results of questionnaire surveys filled by respondents. The sample used is 100 consumers of on line products in Palembang. The method of data analysis uses multiple linear regression analysis. To test the hypothesis the partial effect of independent variables on the dependent variable used the t test. The F test is used to test the effect of the independent variables on the dependent variable together. The results of processing data show there is an influence of product quality on customer satisfaction. Consumer trust affects consumer satisfaction and brand image does not affect consumer satisfaction. Taken together there is the effect of independent variables on the dependent variable. Consumer trust has the most dominant influence on customer satisfaction on line products in Palembang.